How African countries respond to fake news and hate speech - Lisa Garbe; Lisa-Marie Selvik; Pauline Lemaire (Information, Communication & Society, 2021)
While scholars have already identified and discussed some of the most urgent problems in content moderation in the Global North, fewer scholars have paid attention to content regulation in the Global South, and notably Africa. In the absence of content moderation by Western tech giants themselves, African countries appear to have shifted their focus towards state-centric approaches to regulating content. We argue that those approaches are largely informed by a regime's motivation to repress media freedom as well as institutional constraints on the executive. We use structural topic modelling on a corpus of news articles worldwide (N0.167em=0.167em7′787) mentioning hate speech and fake news in 47 African countries to estimate the salience of discussions of legal and technological approaches to content regulation. We find that, in particular, discussions of technological strategies are more salient in regimes with little respect for media freedom and fewer legislative constraints. Overall, our findings suggest that the state is the dominant actor in shaping content regulation across African countries and point to the need for a better understanding of how regime-specific characteristics shape regulatory decisions.
doi:10.6084/m9.figshare.16964966.v1
Keywords: 300; content regulation; fake news; hate speech; Africa; structural topic modelling